Acceleration-Insensitive Pressure Sensor for Aerodynamic Analysis - Zygmunt Szczerba; Piotr Szczerba; Kamil Szczerba; Krzysztof Pytel (Energies, 2023)
This paper presents a method for preparing a pressure sensor that is insensitive to acceleration along with experimental evidence of its efficacy in aerodynamic analysis. A literature review and preliminary studies revealed the undesirable effect of acceleration on sensors that are located on moving elements, as evidenced by deviations from actual pressure values for piezoresistive pressure sensors that are made using MEMS technology. To address this, the authors developed a double-membrane sensor geometry that eliminated this imperfection; a method of implementing two solo pressure sensors as a new geometry-designed sensor was also proposed. Experimental tests of this suggested solution were conducted; these measurements are presented here. The results indicated that this new sensor concept could be used to measure the dynamic pressures of rotating and moving objects in order to obtain measurement results that are more reliable and closer to the true values that are derived from aerodynamic analyses. The published results confirm the reliability of the proposed device.